Cosmic Christology in Paul and the Pauline School Colossians and Ephesians in the Context of Graeco-Roman Cosmology, with a New Synopsis of the Greek Texts - van Kooten, George H. (Mohr Siebeck, 2019)
Reflections on God, Christ and cosmos in the writings of Paul and the Pauline School show that these authors were familiar with important notions from Graeco-Roman cosmology and theology. George van Kooten comes to the conclusion that they might even have adopted a way of thinking in which Judaism and Graeco-Roman cosmology were forged into a new synthesis, and Christ was viewed as a cosmic god. In this development, Paul and the authors of the Pauline School took up various positions which were all represented in contemporary discussions about God and cosmos in the philosophical schools. Against this background this study also sheds new light on the specific relationship between Colossians and Ephesians.